Exploring intercultural competence: A case study of an Indonesian Muslim doctoral student in Australia - Hastowohadi, Hastowohadi; Marifatullloh, Sayid; Maria M. Widiantari (Journal of International Students, 2025)
This study explores the development of intercultural competence through the lived experience of an Indonesian doctoral Muslim student pursuing higher education in Australia. We employ a narrative inquiry case study approach; the research delves into the participant’s personal and academic journey, examining how intercultural interactions in a foreign educational environment shape their understanding and adaptation to cultural differences. The analysis focuses on the linguistic and experiential aspects of the students’ narrative, using transitivity analysis to investigate the processes, actions, and experiences the student describes during their intercultural encounters. Additionaly, language appraisal is employed to assess the student’s emotional responses, attitudes, and evaluations of intercultural situations. This dual analysis provides a comprehensive view of how intercultural competence is constructed and navigated in a cross-cultural context. The findings highlight the dynamic interplay between cultural identity, language, and academic adaptation, offering insights into how students from Indonesia develop intercultural skills in international settings.